Library Strategy in Increasing Reading Interest of Students of State Islamic Senior High School 1, Baubau City, Southeast Sulawesi - Risty Edi; Katni Katni; Riyanto Riyanto (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the strategies implemented by the library of Madrasah Aliyah Negeri 1 Baubau to increase students' reading interest and identify the supporting and inhibiting factors affecting their implementation. Research Method: A qualitative descriptive approach was employed. Data were collected through semi-structured interviews, observations, and document analysis involving library stakeholders and analyzed using data condensation, data display, and conclusion drawing with source triangulation. Results and Discussion: The findings indicate that the library enhances students' reading interest through integrated strategies, including collection development, literacy programs, collaboration with teachers and parents, improved learning facilities, and the use of digital technology. Nevertheless, limited budgets, inadequate digital infrastructure, textbook-dominated collections, and low voluntary reading motivation remain major constraints. Implications: The findings provide practical guidance for strengthening school library management, literacy programs, and policy support for digital infrastructure. Originality: This study offers context-specific evidence on integrated library strategies for promoting reading interest in an Islamic senior high school, highlighting the interaction between library management, literacy innovation, and technology utilization.